Preliminary Study of Trace Elements in Wild Macrofungi from Altos de Cantillana, Central Chile - Segura-Segura, R; Segura-Segura, R; Penagos-Llanos, J; Penagos-Llanos, J (SCIENDO, 2025)
Wild edible mushrooms are a popular food considering their nutritional value. However, some mushroom species can harm human health by accumulating some elements excessively. To evaluate the pollution level of toxic elements in wild edible and non-edible mushrooms from two private natural areas in the Altos de Cantillana mountain range in Central Chile (Altos de Cantillana Natural Reserve and Cerro Poqui Nature Sanctuary) present in them were quantified. All mushrooms contained Pb, Zn, Fe, Cu, and Ni. Mushrooms obtained in Los Altos de Cantillana have higher amounts of metals. In mushrooms of the type Bovista brunnea (sample 27) there are maximum amounts of Pb (566.8 mu g/g), Zn (1152.3 mu g/g), and Cu (568.6 mu g/g) while those of the type Lycoperdon sp. (sample 14) have maximum amounts of Fe (17806.9 mu g/g) and Ni (27.6 mu g/g). On the other hand, only the species Stereum hirsutum (samples 1 and 4) has very low amounts of As (3.9 mu g/g and 6.5 mu g/g) and only this one and Phaeoclavulina flaccida contain low amounts of Cd (0.02 mu g/g and 0.04 mu g/g). On the other hand, Sb and Au were not found in any sample; all values were < LOQ (Limit of quantification). Although intraspecies differences were observed, not all were significant. It is important to highlight the analysis of wild mushroom species that people can consume, such as the genus Cyttaria, which should be evaluated for trace element content.